ANALISIS RASIO LIKUIDITAS DALAM MENGUKUR KINERJA KEUANGAN PADA PT. GARDA TUJU BUANA PERIODE 2021-2022 - Muhammad Riyan Fahlefi; Resame Putri; Ratih Kusumastuti (JURNAL EKONOMI BISNIS DAN MANAJEMEN, 2023)
The purpose of this research is to evaluate the financial performance of PT. Garda Tujuh Buana Tbk during the period 2021 to 2022. In analyzing this financial performance, this study uses the theory of Financial Ratios, where financial ratio analysis will be carried out, especially on Liquidity Ratios, to assess the company's ability to meet short-term debt obligations. The analytical method used in this research is descriptive quantitative analysis. This approach involves calculating the relevant financial ratios in the company using certain formulas. The data and information for this research were obtained from the Indonesia Stock Exchange. The results of the analysis show that the condition of PT. Garda Tujuh Buana Tbk during the last two years from 2021 to 2022 can be said to be not good. The results showed that the level of liquidity ratios for two years obtained results; Current ratio of 55% and 200%, Quitck Ratio of 45% and 149%, Cash Ratio of 20% and 2%..